A Multielement Community Medicine Curriculum for the Family Medicine Clerkship - Bernstein, Rebecca (MedEdPORTAL, 2016)
INTRODUCTION: Many medical schools provide opportunities for students to learn about health disparities, social determinants of health, and the role physicians play in promoting health equity. The family medicine clerkship exposes medical students to these topics to help them understand the health status of patients. A multielement curriculum was incorporated into the core family medicine clerkship to provide the full medical school class exposure to community medicine and was updated in 2014 to increase the emphasis on clinical correlation of community medicine concepts. METHODS: This curriculum consists of a community medicine orientation, a community-based experience, a didactic session, and a reflection paper. The orientation serves as an introduction to the course, and the community-based experience provides hands-on understanding of community medicine. The didactic session encompasses a half-day session of preparatory work, team-based exercises, an interactive lecture, individual reflection, and a seminar-style discussion. Students share their experience with the curriculum in their reflection papers. RESULTS: Since 2014, 286 have students completed the updated curriculum, and reactions have been highly favorable. Most students have agreed or strongly agreed that the sessions met the learning objectives. Student preparation was demonstrated by individual quiz scores (average: 87%, n = 93). Learning and behavior change were evaluated using structured rubric scoring of reflection papers (average: 94%, n = 67). DISCUSSION: Overall, this community medicine curriculum includes a variety of learning experiences for medical students to gain knowledge, attitudes, and skills that are applicable to care in all specialties and may be easily adapted to use in other settings.